A tale for two roles: Root-secreted methyl ferulate inhibits P. nicotianae and enriches the rhizosphere Bacillus against black shank disease in tobacco - Ma, Siqi; Chen, Qianru; Zheng, Yanfen; Ren, Tingting; He, Rui; Cheng, Lirui; Zou, Ping; Jing, Changliang; Zhang, Chengsheng; Li, Yiqiang (Microbiome, 2025)
Root exudates serve as chemical signaling molecules that regulate rhizosphere interactions and control soil-borne diseases. The interactions between plants and the soil microbiome play dynamic and crucial roles in regulating the resistance of plants to biotic stress. However, the specific roles of many root exudates in plant pathogens remain unclear. The root exudate methyl ferulate, a naturally occurring and relatively non-toxic antifungal agent, has been applied to control postharvest pathogens and preserve foodstuffs and has not been used in plant disease control. This study investigated the role of the root exudate methyl ferulate in controlling tobacco black shank disease. We observed that methyl ferulate was secreted in greater quantities in the tobacco resistant cultivar Gexin 3 following inoculation with P. nicotianae than in the susceptible cultivar Xiaohuangjin 1025. Our findings also revealed that methyl ferulate strongly inhibited P. nicotianae (EC = 67.51 µg/mL), effectively controlling tobacco black shank disease by impairing NADH dehydrogenase function (the activity decreased by 50%). Furthermore, methyl ferulate recruited disease-suppressive rhizosphere microbes, such as Bacillus (the relative abundance of these microbes increases from 4.69% to 13.79%), thereby increasing disease resistance. The overexpression of caffeic acid O-methyltransferase NtCOMT10 resulted in increased methyl ferulate secretion (increased to 221.09% compared with that of the wild-type), concomitant improvement in the disease suppression of tobacco black shank disease (disease index decreased from 20% to less than 10%) and enrichment of beneficial microbes. In addition, methyl ferulate exerted antagonistic effects on other phytopathogens, such as B. cinerea, P. aphanidermatum, P. sojae, C. lagenarium and F. oxysporum. Our findings indicated that methyl ferulate, a component of root exudates regulated by NtCOMT10, can inhibit phytopathogens and enrich rhizosphere Bacillus against plant disease. The great dual effect of methyl ferulate on the control of phytopathogens and its low cost enable a novel potential avenue for controlling soil-borne fungal diseases. This study provides ingenious insights into controlling soil-borne diseases through beneficial root exudates. Video Abstract.